Two field experiments on self-selection, collaboration intensity, and team performance - Mira Fischer; Rainer Michael Rilke; B. Burcin Yurtoglu (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We analyze how the team formation process influences the ability composition and performance of teams, showing how self-selection and random assignment affect team performance for different tasks in two natural field experiments. We identify the collaboration intensity of the task as the key driver of the effect of self-selection on team performance. We find that when the task requires low collaborative efforts, the team performance of self-selected teams is significantly inferior to that of randomly assigned teams. When the task involves more collaborative efforts, self-selected teams tend to outperform randomly assigned teams. We observe assortative matching in self-selected teams, with subjects more likely to match with those of similar ability and the same gender.
Keywords: I21; M54; C93; 330; Team Performance; Self-selection; Field Experiment; Education